Modeling of the hand–arm system for impact loading in shear fastener installation - Joshi, Akul; Guttenberg, Robert; Leu, Ming; Murray, Susan (International journal of industrial ergonomics, 2008)
The aim of this study is to model the hand–arm system during fastening operation using shear fasteners. This fastening operation has considerable dynamic forces caused by the impact delivered to the hand–arm at the end of the operation because of fastener shear-off. The hand–arm is modeled as a rotational single-degree-of-freedom system. The values of the model parameters are obtained using the magnitude of compliance spectrum calculated from the measured torque and angular displacement data, which are obtained while installing fasteners on a fixtured experimental setup, and by a non-linear least-square curve fitting technique. The experimental setup facilitates transferring the torque from a torque driver to a fastening tool handle held by the subject. The identified parameter values are found consistent for the trials conducted under same test conditions. Strong agreements are seen between the predicted responses using the model and the measured responses. This study is useful in tool selection and workplace design for assembly shop floors where hand-held power tools are commonly used. It demonstrates a systematic approach in predicting the motion of an operator's hand–arm for a given torque impulse produced by a fastening tool. The predicted motion can be used for further analysis to determine the detrimental effect it may have in causing cumulative trauma disorders.